(untitled) (Brazilian Journal of Oceanography, 2010)
An oceanographic campaign was conducted in the Araranguá river estuary during the period from May 11th to 13th of 2006 in order to produce a first hydrographic characterization of this system. The campaign was carried out during the spring tide period, and coincidentally after an intense rain event in the region which produced a peak in river discharge. Water level, currents and salinity time series were recorded hourly during a 50-hour period, at a site nearly 7 km upstream from the estuarine mouth. Two longitudinal distributions of salinity along the estuary were also recorded. The hydrographic data time-series were used to compute the advective salt flux in order to investigate the changes in the transport terms as a function of the change in discharge. The results showed that the estuarine structure was strongly modulated by the river discharge. The drop in water level of about 0.5 m during the first 24 hours was directly related to the ebb phase of the river flood. The water column was highly stratified throughout the period, therefore the stratification increased during the last 24 hours. The currents were stronger, ebbing and uni-directional at the beginning and became weaker and bidirectional as the water level went down, assuming a tidal pattern. The total salt transport in the first 25 hours was of -13.6 kg.m-1.s-1 (seawards), decreasing to 3 Kg.m-1.s-1 during the last 25 hours (landwards). It was also noticeable that the pH in the estuary, recorded together with the salinity, was around 5, showing that the water quality in the estuary is affected by the coal mining activity in the hydrographic basin.